Quantification of the effect of Lipo-PGE1 on angiogenesis. Issue 1 (January 2015) - Eo, SuRak; Kwon, Chan; Lee, HyunJic; Cho, SangHun; Kim, JinYoung; Baek, GooHyun; Yeo, JeongSeok; Lim, ChiYeon
Summary Fifteen rabbits were used to assess the effect of Lipo-PGE1 on neovascularization. Merocel® and Alloderm® of the same size were implanted separately under the back skin to act as matrices for vessel growth. Lipo-PGE1 was injected intravenously for 2 weeks in an experimental group of eight rabbits, and they were compared with a control group of seven untreated animals. Blood flow was measured using the 99mTcO4− clearance technique. The mean blood clearance halftime (T1/2) and washout radioactivity were measured. Newly formed vessels were counted by CD31. The mean clearance halftime was 4005 ± 2161.3 and 13840 ± 4644.6 s in the experimental and control group, respectively, in the 1 × 2 × 1.5-cm-sized implants (p = 0.0125), and 1560 ± 1174.7 and 3405 ± 807.03 s, respectively, in the 2 × 2 × 1.5-cm-sized implants (p = 0.0413). Histological examinations revealed that the mean numbers of newly formed vessels in the experimental and control groups were 11 ± 1.58 and 7.8 ± 1.71, respectively, in the 1 × 2 × 1.5-cm-sized implants (p = 0.0501), and 20.19 ± 12.47 and 12.33 ± 3.25, respectively, in the 2 × 2 × 1.5-cm-sized implants (p = 0.02679). Lipo-PGE1 was found to be effective in promoting angiogenesis in a rabbit matrix model.